2019
DOI: 10.24200/amecj.v2.i03.66
|View full text |Cite
|
Sign up to set email alerts
|

A review: Water pollution by heavy metal and organic pollutants: Brief review of sources, effects and progress on remediation with aquatic plants

Abstract: Heavy metals and organic pollutants are ubiquitous environmental pollutants affecting the quality of soil, water and air. Over the past 5 decades, many strategies have been developed for the remediation of polluted water. Strategies involving aquatic plant use are preferable to conventional methods. In this study, an attempt was made to provide a brief review on recent progresses in research and practical applications of phytoremediation for water resources with the following objectives: (1) to discuss the tox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(26 citation statements)
references
References 110 publications
0
25
0
1
Order By: Relevance
“…Aquatic plants could be used as bioindicators of BPA toxicity [27]. In this sense, Cymodocea nodosa (Ucria) Ascherson 1870, one of the five most widespread Mediterranean seagrass species [28] and belonging to the taxonomic families required for the determination of a Species Sensitivity Distribution (SSD) (EU Technical Guidance Document of the European Union (EU), 2003) [29], can act as one BPA "bioindicator" organism [25].…”
Section: Introductionmentioning
confidence: 99%
“…Aquatic plants could be used as bioindicators of BPA toxicity [27]. In this sense, Cymodocea nodosa (Ucria) Ascherson 1870, one of the five most widespread Mediterranean seagrass species [28] and belonging to the taxonomic families required for the determination of a Species Sensitivity Distribution (SSD) (EU Technical Guidance Document of the European Union (EU), 2003) [29], can act as one BPA "bioindicator" organism [25].…”
Section: Introductionmentioning
confidence: 99%
“…Removing these chemicals from water resources or wa s tewater before they are released into the environment is essential to prevent potential harm to humans and ecosy s tems. Various methods are available for removing PCP and TCP from water, including biological and physicochemical approaches such as photochemi s try, air s tripping, incineration, and adsorption technologies using activated clay and plant-based carbons [7]. While some of these methods are effective, they can be challenging to implement.…”
Section: Introductionmentioning
confidence: 99%
“…While some of these methods are effective, they can be challenging to implement. Using aquatic plants for wa s tewater treatment is a newer method for removing pollutants, and s tudies have shown that it can be effective when using con s tructed wetlands, pilot-scale sy s tems, or hydroponic setups [7]. The efficiency of plantbased treatment sy s tems can vary depending on the specific plant species and their productivity.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmed Shahid studied water pollution and its source, impact and management through a case study in Delhi [2]. Obinna Isiuku Beniah briefly reviewed the source, impact and progress in the use of aquatic plants for remediation of water pollution caused by heavy metals and organic pollutants [3]. Mekonnen Mesfin M discussed the phosphorus load of global human activities on fresh water and the related gray water footprint and water pollution level [4].…”
Section: Introductionmentioning
confidence: 99%